Hubungan Hypnobirthing dengan Tingkat Kecemasan Pada Ibu Hamil - Hasanah Pratiwi Harahap; Winda Agustina (Universitas Islam Jember, 2026)
The prevalence of depression and anxiety risk in facing vaginal delivery in Indonesia in 2025 is estimated to range from 10–25%, particularly among women aged 20–44 years. These conditions can inhibit the labor process by approximately 10–15%. Among mothers undergoing cesarean section, anxiety levels are reported to reach 15–25%. This study aims to analyze the relationship between hypnobirthing and anxiety levels in pregnant women at Aini Clinic, Medan. The method used was an analytical survey with a cross-sectional approach. The study population consisted of all pregnant women participating in hypnobirthing, totaling 30 respondents, using a total sampling technique. Data analysis was performed using univariate and bivariate methods with the chi-square test. The results showed that most respondents did not routinely participate in hypnobirthing, accounting for 18 individuals (60%), and the majority experienced moderate levels of anxiety, totaling 12 individuals (40%). The chi-square test result showed a p-value of 0.018 with a significance level of α = 0.05 (p < α), indicating a significant relationship between hypnobirthing and anxiety levels in pregnant women. In conclusion, hypnobirthing is associated with anxiety levels in pregnant women. Therefore, pregnant women are encouraged to actively participate in hypnobirthing classes during pregnancy.